Correlation of Informal Study Frequency and English Reading Proficiency Among EFL Learners - Revi Nauval Ilhansyah; Triono Budi Nugroho; Muhammad Romdoni; Abdul Syahid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study investigates the relationship between informal study frequency and test scores among English as a Foreign Language (EFL) learners to determine whether non-traditional study habits contribute to academic performance. Employing a correlational research design, data were collected from a sample of EFL learners through self-reported study frequency surveys and standardized English test scores. The Spearman’s rank correlation coefficient was used to analyze the data, given the non-normal distribution of the variables. The results reveal no statistically significant correlation between informal study frequency and test scores, as indicated by a weak Spearman’s rho and a high p-value. These findings suggest that informal study habits may not directly influence test performance in the observed sample, emphasizing the complexity of factors affecting EFL learners’ academic outcomes. While informal learning remains an essential aspect of language acquisition, its measurable impact on standardized assessments warrants further investigation. Future research could benefit from a larger sample size and the inclusion of additional variables, such as formal study practices, learner motivation, or access to resources, to provide a more comprehensive understanding of how various factors interact to influence EFL test performance. This study highlights the importance of cautious interpretation when analyzing the role of informal learning in academic achievement.